Anaphora and Cataphora References in Netflix Series Locke and Key - Juan Franco Kolo Sae; I Nengah Laba; Ni Luh Desy Suari Dewi (LPPM Universitas Dhyana Pura, 2022)
AbstrakPenelitian ini bertujuan untuk mengetahui jenis-jenis referensi anafora dan katafora dalam dialog Netflix Series Locke and Key. Penelitian ini menggunakan teori Ruslan Mitkov (2013) untuk enam jenis referensi anafora: pronominal anaphoric, lexical now anaphoric, noun anaphoric, verb anaphoric, adverb anaphoric, zero anaphoric. Teori Yule (1996) untuk referensi cataphora. Metode kualitatif yang digunakan dalam penelitian ini dimana data diambil dari serial dialog Locke and Key yang dapat diakses dari website resmi Netflix. Analisis menunjukkan dalam seri ini dengan perhitungan data 58 temuan dengan klasifikasi. 26 references in pronominal anaphoric, 12 references in lexical noun phrase, 2 references in noun anaphoric, 3 references in verb anaphoric, 3 references in adverb anaphoric, 2 references in zero anaphoric and 10 references in cataphora.Kata kunci: Pragmatic, Anaphora and cataphora reference, Netflix series.AbstractThis study aims to find out the types of anaphora and cataphora references in dialogue Netflix Series Locke and Key. This study used the Ruslan Mitkov’s (2013) theory for the six types of anaphora references: pronominal anaphoric, lexical now anaphoric, noun anaphoric, verb anaphoric, adverb anaphoric, zero anaphoric. Yule’s (1996) theory for the cataphora references. The qualitative method was used in this study where the data was taken from dialogue series Locke and Key that can be accessed from official Netflix website. The analysis showed in this series whit the calculation of the data 58 findings with the classification 26 references in pronominal anaphoric, 12 references in lexical noun phrase, 2 references in noun anaphoric, 3 references in verb anaphoric, 3 references in adverb anaphoric, 2 references in zero anaphoric and 10 references in cataphora.Keywords: Pragmatic, Anaphora and cataphora reference, Netflix series.